2012
DOI: 10.1021/es204279u
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic Decomposition of Perfluorooctanoic Acid by Indium Oxide and Its Mechanism

Abstract: Perfluorooctanoic acid (C(7)F(15)COOH, PFOA) has increasingly attracted worldwide concerns due to its global occurrence and resistance to most conventional treatment processes. Though TiO(2)-based photocatalysis is strong enough to decompose most organics, it is not effective for PFOA decomposition. We first find that indium oxide (In(2)O(3)) possesses significant activity for PFOA decomposition under UV irradiation, with the rate constant about 8.4 times higher than that by TiO(2). The major intermediates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(143 citation statements)
references
References 53 publications
5
135
0
3
Order By: Relevance
“…According to a previous study [13], the concentration of fluoride ions generated in the degradation samples was monitored with an ion chromatography system (Dionex ICS-2000) equipped with a degasser, an autosampler, a guard column (IonPac AG11-HC), a separation column (IonPac AS11-HC), a column heater (30 ∘ C), and a conductivity detector with a suppressor. The mobile phase was an aqueous solution of KOH (30 mmol/L) with a flow rate of 1.0 mL/min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a previous study [13], the concentration of fluoride ions generated in the degradation samples was monitored with an ion chromatography system (Dionex ICS-2000) equipped with a degasser, an autosampler, a guard column (IonPac AG11-HC), a separation column (IonPac AS11-HC), a column heater (30 ∘ C), and a conductivity detector with a suppressor. The mobile phase was an aqueous solution of KOH (30 mmol/L) with a flow rate of 1.0 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the development of affinity media that selectively removes PFCs from water and wastewater is of significant interest. Some researchers have reported that TiO 2 alone displays low degradation capacity for organic compounds [9,13]. Many studies seek to hybridize TiO 2 with selective adsorbents leveraging the advantages of both materials.…”
Section: International Journal Of Photoenergymentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering solutions using oxidants and catalysts have been developed to degrade PFCAs on a small scale in the lab. For example, UV photo-oxidation with indium oxide (In 2 O 3 ) as the catalyst is effective for PFOA degradation [11], but these processes will not occur in the natural environment.…”
Section: Perfluoroalkyl Carboxylic Acids (Pfcas) and Their Precursorsmentioning
confidence: 99%
“…Indium oxide (In 2 O 3 ) exhibits remarkable photocatalytic activity for PFOA decomposition. The tightly bidentate compound or the bridging configuration of PFOA molecule to the In 2 O 3 surface enhances the direct decomposition of PFOA by photogenerated holes in In 2 O 3 under UV irradiation (Li et al, 2012a). Nanostructured In 2 O 3 with greater oxygen vacancy defects shows higher photocatalytic activity (Li et al, 2012b(Li et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%